EZH2-Mediated Epigenetic Suppression of GDF15 Predicts a Poor Prognosis and Regulates Cell Proliferation in Non-Small-Cell Lung Cancer - Xiyi Lu; Xuezhi He; Jun Su; Jing Wang; Xinyin Liu; Kun Xu; Wei De; Erbao Zhang; Renhua Guo; Yuenian Eric Shi (Elsevier, 2018)
Growth differentiation factor 15 (GDF15), a member of the TGF-β superfamily of cytokines, has been reported to exert very heterogeneous functions in various tumors. However, its expression and roles in mediating non-small-cell lung cancer (NSCLC) progression remain unknown. In this study, we found that GDF15 is downregulated in paired NSCLC tissues and correlated with poor clinical outcomes in NSCLC. A functional experiment demonstrated that overexpression of GDF15 significantly repressed NSCLC proliferation both in vitro and in vivo. Mechanistic studies reveal that inhibition of EZH2 expression prevented its binding to the GDF15 promoter region and reduced the trimethylation modification pattern of H3K27. Together, our data uncover that GDF15 is a direct target of EZH2 and, as a regulator of proliferation, might serve as a candidate prognostic biomarker and target for new therapies in human NSCLC. Keywords: EZH2, epigenetic, GDF15, cell proliferation, NSCLC